Peningkatan Motivasi Belajar Matematika Melalui Strategi Team Quiz dengan Media Kardus Pada Siswa Kelas IV SD N 2 Pucang Klaten Tahun Pelajaran 2015/2016 - Yuniantika, Trisna (2016)
This study aims to increase the motivation to learn mathematics by implementing strategy Team Quiz with cardboard media on fourth grade students N 2 Pucang. This type of research is the PTK (Classroom Action Research). The subjects were students fourth grade N 2 Pucang totaling 21 students. Data was collected through interviews, observation and documentation. The test validityusing triangulation resources and engineering. Data analysis was performed with 4 stages: data collection, data reduction, data display and conclusion. The results showed an increase motivation to learn in mathematics. This can be evidenced by the achievement indicators of learning motivation as follows: Readiness students in learning to follow increase from 38.09% (pra cycle) to 85.71% (cycle II the second meeting). Activity of students in group discussions increase from 33.33% (pra cycle) to 80.95% (cycle IIthe second meeting). Student activity in expression, ask and answer questions increased from 33.33% (pra cycle) to 76.19% (cycle II the second meeting). Student independence in doing exercises increase from 47.61% (pra cycle) to 85.71% (cycle II the second meeting). Accuracy in doing exercises increase from 33.33% (pra cycle) to 80.95% (cycle II the second meeting). The study concluded that the implementation strategy Team Quiz with cardboard media can enhance students' motivation to learn mathematics in fourth grade N 2 Pucang lesson year 2015/2016. Keyword:Cardboard media, motivation to learn, strategy Team Quiz.